2004
DOI: 10.2519/jospt.2004.34.9.504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Taping on Pain and Function in Patellofemoral Pain Syndrome: A Randomized Controlled Trial

Abstract: Study Design: A randomized controlled trial. Objectives: To investigate the effectiveness of daily patella taping and exercise on pain and function in individuals with patellofemoral pain syndrome. Background: Patella taping and muscle-strengthening programs are commonly used to treat patellofemoral pain syndrome. There is, however, little evidence for the effectiveness of these approaches. Methods and Measures: Twenty-four men and 6 women aged 17 to 25 years (mean ± SD, 18.7 ± 1.2 years) participated in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 38 publications
3
57
1
3
Order By: Relevance
“…The identification of these impairments would seem to support the incorporation of hip strengthening exercises into the rehabilitation of patients with unilateral PFPS. Previously mentioned clinical trials 4,29 and case reports 17 that included hip strengthening exercises in their multimodal rehabilitation programs have been successful in reducing the pain and disability associated with PFPS. Further research is warranted to determine whether hip strengthening and/or endurance exercises are a necessary component of a multimodal rehabilitation program for patients with PFPS and to identify which subgroup of patients with PFPS is most likely to respond to these types of therapeutic activities.…”
Section: Results Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of these impairments would seem to support the incorporation of hip strengthening exercises into the rehabilitation of patients with unilateral PFPS. Previously mentioned clinical trials 4,29 and case reports 17 that included hip strengthening exercises in their multimodal rehabilitation programs have been successful in reducing the pain and disability associated with PFPS. Further research is warranted to determine whether hip strengthening and/or endurance exercises are a necessary component of a multimodal rehabilitation program for patients with PFPS and to identify which subgroup of patients with PFPS is most likely to respond to these types of therapeutic activities.…”
Section: Results Dmentioning
confidence: 99%
“…Specific activities targeting performance of the lateral hip musculature have been incorporated into physical therapy intervention programs for improving pain, disability, and function in patients with PFPS. 4,17,29 In spite of the fact that intervention programs for the management of patients with PFPS include exercises aimed at improving the performance of the lateral hip musculature, we are aware of only 2 research reports that have investigated whether differences in hip strength exist between patients with PFPS and a control group. 12,20 Ireland et al 12 found that 15 female subjects with PFPS demonstrated 26% less hip abduction strength and 36% less hip external rotation strength when compared to 15 age-matched control subjects.…”
Section: 726mentioning
confidence: 99%
“…Whittingham et al [52] showed significant large to very large effects favouring four weeks of patella taping and exercise over exercise alone (2.47, 1.25 to 3.70), and over placebo tape with exercise (1.35, 0.36 to 2.35). In contrast, longer-term data from Clark et al [43] showed no significant between-group effects when patella taping and education was compared to education alone, and when patella taping was added to exercise and education (12 and 52 weeks).…”
Section: Patella Tapingmentioning
confidence: 99%
“…9 Since McConnell's landmark paper, 43 several clinical trials demonstrated that patellar taping can be an effective part of an intervention plan for reducing pain and improving function in patients with PFPS, but effect sizes vary. 2,8,48,66,67 While evidence suggests that taping can be effective, no published study has identified specific clinical examination variables that are predictive of which patients with the condition will respond successfully to patellar taping. Identification of these variables would provide clinicians with a useful clinical decision-making tool and may help increase the efficacy of the technique.…”
mentioning
confidence: 99%
“…One technique that has gained acceptance as an effective component of treatment for anterior knee pain is patellar taping. 8,43,67 Australian physical therapist Jenny McConnell developed patellar taping and reported a 96% success rate using taping as a component of a treatment regimen for PFPS. 43 The approach is based largely on the premise that patellar malalignment and a poorly tracking patella can lead to patellofemoral pain.…”
mentioning
confidence: 99%